2007
DOI: 10.1002/ceat.200600398
|View full text |Cite
|
Sign up to set email alerts
|

Practical Assessment of Electronic Water Treatment for the Prevention of Fouling

Abstract: Fouling or scaling, i.e., the occurrence of deposits on tubes, heat exchangers, and other devices, is a common problem in industrial and domestic processes. Many anti-fouling techniques exist, both chemically and non-chemically. The efficiency of non-chemical methods is still controversial, although the use of these devices is already widespread in industry. In this contribution, a case study is presented in which the operation of such a device is demonstrated. The electronic water treatment device under study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Various techniques have been employed to treat mixing water in research, including mechanical, chemical, thermal, electrical, and magnetic treatment [9][10][11][12][13]. Many studies revealed that magnetic treatment, in particular, shows promising potential in activating the behavior of cementbased construction materials [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been employed to treat mixing water in research, including mechanical, chemical, thermal, electrical, and magnetic treatment [9][10][11][12][13]. Many studies revealed that magnetic treatment, in particular, shows promising potential in activating the behavior of cementbased construction materials [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…There are many researchers do a lot of qualitative researches based on the above-mentioned antifouling mechanism of EAF system [6][7][8][9][10][11]. But to the best knowledge, none of research works about controlling the induced electric field acted on the solution by EAF system have been done yet by now.…”
Section: Introductionmentioning
confidence: 99%